Terminology of the aerospace industry: systemic and structural features - O. Yu. Ivanchina (Вестник Самарского университета: История, педагогика, филология, 2023)
This article presents an attempt to describe systemic and structural features of contemporary English-language aerospace terminology. Relevance of this terminological system study is determined by rapid development of aerospace industry. Its terminology is expanding rapidly as well. Specifically, existing terms acquire new conceptual meanings; new concepts appear as well as terms to convey them; concepts and terms from adjacent domains are borrowed; general language words become specialized knowledge units within the framework of specific terminological system. The purpose of this study is to describe systemic features of aerospace terminology from the perspective of basic requirements to terms, as well as to describe structural features of terms in question. Terminological units are subject to linguistic analysis, which can be carried out in a number of ways. To conduct the research aiming at describing aerospace terminology as a system, the author used definitional, structural and statistical methods. The terminological system of the industry in question is based on «genus proximum et differentia specifica» principle. It is also marked by the presence of polysemous, homonymous, and synonymic terms. As for the structural features, there are both monolexemic and polylexemic terms: monolexemic terms cover basic, derived, and compound terms with predominance of simple terms; polylexemic terms comprise two-component, three-component, and multicomponent terms with predominance of two-component terms. Most polylexemic terms have abbreviations. Abbreviations are omnipresent in the aerospace industry terminology: on the one hand, they simplify specialized communication; on the other hand, abbreviations prevent non-specialists from understanding the aerospace discourse.